Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Badan Pengawas Pemilihan Umum Kabupaten Lebong - Alpin Alpin; Siti Hanila; Yudi Irawan Abi (Jurnal Fokus Manajemen, 2023)
The purpose of this study was to determine the effect of workload and work environment on employee performance at the General Election Supervisory Board in Lebong Regency.The sample in this study was all employees at the Election Supervisory Board for Lebong Regency as many as 32 people consisting of 10 civil servants and 22 honorary people. Data collection using a questionnaire and the method of analysis used is multiple linear regression, determination test and hypothesis testing. The results of the regression analysis showed Y = 18.535 - 0.037X1 + 0.583 X2, this illustrates a positive regression direction, meaning that there is a positive influence between X1 (workload) and X2 (work environment) on performance (Y). Means that if the workload and work environment variables increase, performance will increase. The magnitude of the coefficient of determination is 0.297. This means that X1 (workload) and X2 (work environment) have an effect on performance (Y) of 29.7% while the remaining 70.3% is influenced by other variables not examined in this study. The results of the t test at a significance level of 0.05 explained that partially the workload and work environment variables had a significant influence on the performance variables of the Election Supervisory Board for Lebong Regency. The results of the F test at a significance level of 0.05 explain that the workload and work environment variables have a simultaneous (together) influence on performance at the General Election Supervisory Board of Lebong Regency.